Role of GATA3 as a potential adjunct marker in the differential diagnosis of Paget's disease of the nipple - Tércia Jovino Neves Santos; Marina De Brot; Stephania Martins Bezerra; Samuel Rodrigues Buniatti; Victor Piana de Andrade; Fernando Augusto Soares; João Víctor Alves de Castro; Cynthia Aparecida Bueno de Toledo Osório (BMC, 2022)
Abstract Aims Paget's disease of the nipple (PDN) is a rare type of cancer of the nipple-areola complex. We examined GATA3 protein expression in PDN to determine its potential value as an adjunct marker in the differential diagnosis with other nipple lesions. Methods and results Chart review documented clinicopathological data. H&E slides were re-evaluated and immunohistochemistry (IHC) for GATA3 was performed. Amongst 3614 breast cancer patients, 74 had PDN and 41 cases were selected for our study (mean age, 55 years). Amid PDN cases, 4 (10%) patients showed PDN alone, 22 (65%) had an underlying ductal carcinoma in situ and 15 (37%) had invasive breast carcinomas (IBC), including 11 invasive carcinoma of no special type, 2 lobular, 1 mucinous and 1 micropapillary carcinoma. Additionally, 9 cancers were classified as luminal B, 4 as HER2 overexpression and 2 as luminal A. GATA3 expression was detected in all 41 PDN cases and in all underlying cancers. Furthermore, IHC for S-100, HMB45 and Melan-A was performed in PDN-only, ensuing negative results. Positivity for cytokeratin 7 or AE1/AE3 was demonstrated in all cases and HER2 overexpression was seen in 2/4 lesions. GATA3 expression was noted in all lesions, including one CK7-negative case. Conclusion Our findings indicate that GATA3 is consistently expressed in PDN. Although not entirely specific, positivity for GATA3 reinforces the non-melanocytic nature of PDN and its mammary origin, thus representing a potential adjunct tool for the diagnosis of PDN in tricky situations, particularly PDN variants or unusual lesions.